2009
DOI: 10.1017/s0967199409990190
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of the embryonic development inBrycon cephalus(Günther, 1869)

Abstract: SummaryThe embryogenesis of Brycon cephalus was established in seven stages: zygote, cleavage, blastula, gastrula, segmentation, larval and hatching, in an incubation period of 11 h (26 • C). The zygote phase was observed directly after fertilization and egg hydration. Cleavage began at 0.5 h of incubation and extended up to the morula phase (1.5 h; +100 blastomeres). Cleavage was meroblastic and underwent the following division pattern: the first five divisions were vertical and perpendicular to each other, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 21 publications
3
31
0
5
Order By: Relevance
“…The micropyle is a small opening in the zona radiata, composed of the vestibule and micropylar channel that reaches the oocyte's plasmatic membrane and participates in the fertilization process (Ganeco and Nakaghi, ). In this study, oocytes of both species showed a funnel‐shaped micropyle, a common pattern similar to other Characiformes species (Ganeco et al., ; Alexandre et al., ; Isaú et al., ).…”
Section: Discussionsupporting
confidence: 86%
“…The micropyle is a small opening in the zona radiata, composed of the vestibule and micropylar channel that reaches the oocyte's plasmatic membrane and participates in the fertilization process (Ganeco and Nakaghi, ). In this study, oocytes of both species showed a funnel‐shaped micropyle, a common pattern similar to other Characiformes species (Ganeco et al., ; Alexandre et al., ; Isaú et al., ).…”
Section: Discussionsupporting
confidence: 86%
“…In jahu, the blastomeres become smaller as their number increase (Marques, 2008), a condition which is also observed in other teleosts: Prochilodus lineatus (NinhausSilveira et al, 2006), Brycon cephalus (Alexandre et al, 2009).…”
Section: Discussionmentioning
confidence: 73%
“…Brycon nattereri embryogenesis can be considered as long compared with other species of the genus Brycon, such as B. cf. erythropterus (Eckmann, 1984), B. orbignyanus (Nakatani et al, 2001), B. insignis (Andrade-Talmelli et al, 2001;Isaú et al, 2013), B. siebenthalae (Clavijo-Ayala & Arias-Castellanos, 2004), B. orthotaenia (Gomes et al, 2013) and B. cephalus (Alexandre et al, 2010) in which embryonic development was concluded between 11 and 30 h after fertilization, at 23 to 28°C (Table 3). Temperature is the main factor controlling the development rate of fish (Kamler, 1992).…”
Section: Discussionmentioning
confidence: 99%